Theoretical justification of the influence of change of dilaton and compression bonds of atoms of materials of machine parts on their tribological effect - Aulin, V.V.; Lysenko, S.V.; Hrinkiv, A.V.; Derkach О.D.; Makarenko D.О.; Zhylova І.V. (Problems of Tribology, 2021)
The course of friction and wear processes in the surface layers of conjugations of machine parts is clarified on the basis of the idea of dilaton and compression bonds of atoms in the materials of parts. Dilaton-compression connections are random in nature, and therefore in this work the theory of destruction of parts by S.M. Zhurkov, thermodynamic and quantum physical approaches. The entropy at the macro-, meso- and microscopic levels and the local regions of the materials of conjugation of the parts subject to friction loading are considered. In the diagram of the state of atomic-molecular bonds the dependence curve Fi(ri) or Ti(ri) is considered and the analysis of transformations of bonds according to the specified diagram is carried out. From the point of view of solid state physics and tribophysics, the manifestation, evolution and consequences of the influence on the characteristics and properties of the friction zone of dilaton and compression bonds of material atoms are considered. Composite materials (composite coatings) are substantiated in more detail. This takes into account the assessment of the concept of material stresses in the friction zone, the ability to relax it, as well as the presence of the SD effect. The fracture process is associated with the modulus of elasticity of the components of the composite material and the bulk content of the filler. An appropriate condition is proposed, which determines the tribological efficiency of composite materials and coatings